2014
DOI: 10.1039/c4ra06522k
|View full text |Cite
|
Sign up to set email alerts
|

Isomorphous substitution of Cr by Fe in MIL-101 framework and its application as a novel heterogeneous photo-Fenton catalyst for reactive dye degradation

Abstract: Partial isomorphous substitution of Cr by Fe in the MIL-101 framework was achieved by direct synthesis using a hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(43 citation statements)
references
References 37 publications
4
39
0
Order By: Relevance
“…In addition, the Cr 2p spectra (Fig. S3) exhibit that the oxidation states of Cr in the electrocatalysts are assigned to Cr III (Cr 2p 3/2 at~576.6 eV and Cr 2p 1/2 at~586.4 eV), which agrees with the ones in MIL-101(Cr) [41,57]. It is indicating that the oxidation states of Cr in the support MIL-101(Cr) almost keep unchanged during the preparation of the electrocatalysts.…”
Section: Electrocatalytic Propertiessupporting
confidence: 72%
“…In addition, the Cr 2p spectra (Fig. S3) exhibit that the oxidation states of Cr in the electrocatalysts are assigned to Cr III (Cr 2p 3/2 at~576.6 eV and Cr 2p 1/2 at~586.4 eV), which agrees with the ones in MIL-101(Cr) [41,57]. It is indicating that the oxidation states of Cr in the support MIL-101(Cr) almost keep unchanged during the preparation of the electrocatalysts.…”
Section: Electrocatalytic Propertiessupporting
confidence: 72%
“…The weak peak at 1106 cm 21 and sharp peak at 745 cm 21 are lined with r(C-H) and c(C-H) vibration of aromatic rings, respectively. 63 For the fresh [Bmim][OAc] (Figure 2b), the band at 1572 cm 21 , attributed to the vibration of C5O of acetate, slightly right shifts compared with the C5O band of MIL-101(Cr). It has been indicated that the acetate anion is strongly interacting with the imidazolium cation through C-2 hydrogen.…”
Section: Resultsmentioning
confidence: 98%
“…For this study, Qiao Sun et al modified the MIL-53(Fe) by adding Mn, Co, and Ni metal into the framework of MIL-53(Fe) material, which exhibited excellent catalytic performance in liquid-phase degradation of phenol [30]. Various rare-earth or transition metals that modify MOFs structures have recently been reported such as three-dimensional Ln(III)-Zn(II) heterometallic coordination polymers [31], Fe substituted Cr MIL-101 [32], Ag-doped MOF-like organotitanium polymer (Ag@NH2-MOP(Ti)) [33], Ti-doped UiO-66 [34], Eu substituted Fe MIL-53 [35], and Zn-Ln coordination polymers (Ln = Nd, Pr, Sm, Eu, Tb, Dy) [36].…”
Section: Introductionmentioning
confidence: 99%